2022
DOI: 10.3390/cells11233836
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Induced HIF-1α Expression Promotes Neurogenic Bladder Fibrosis via EMT and Pyroptosis

Abstract: Background: Neurogenic bladder (NB) patients exhibit varying degrees of bladder fibrosis, and the thickening and hardening of the bladder wall induced by fibrosis will further affect bladder function and cause renal failure. Our study aimed to investigate the mechanism of bladder fibrosis caused by a spinal cord injury (SCI). Methods: NB rat models were created by cutting the bilateral lumbar 6 (L6) and sacral 1 (S1) spinal nerves. RNA-seq, Western blotting, immunofluorescence, cell viability and ELISA were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Every rat was a separate experiment unit because of the intervention experiment. Based on the analysis of PASS 15.0 and the primary data collected for our prior study and pre-experiments, whose set power and were 0.85 and 0.05, the sample size was determined [ 14 ]. There were no predetermined inclusion or exclusion criteria that were stated explicitly.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Every rat was a separate experiment unit because of the intervention experiment. Based on the analysis of PASS 15.0 and the primary data collected for our prior study and pre-experiments, whose set power and were 0.85 and 0.05, the sample size was determined [ 14 ]. There were no predetermined inclusion or exclusion criteria that were stated explicitly.…”
Section: Methodsmentioning
confidence: 99%
“…The samples were then divided into sections that were four micrometers thick. Using traditional staining techniques, Masson trichrome and H&E staining were used in the sections to analyze the histomorphology of the rat bladder [ 14 ]. The ImageJ programme (V 1.8.0.112) assessed collagen accumulation (% of total area) in Masson’s stained sections.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Referring to the immunofluorescence experimental procedure described by Li et.al 19 , RAW264.7 cells in different groups were fixed, permeated, blocked, and then incubated with NLRP3 (Cat No. MA5-23919; 1:200) and IL-18 (Cat No IPB0723; 1:200) primary antibodies at 4 °C overnight.…”
Section: Immunofluorescencementioning
confidence: 99%
“…Recently, the change in the EMT was observed in the keloid tissues [ 120 ]. Li et al [ 121 ] demonstrated that hypoxia-induced HIF-1α expression significantly promoted neurogenic bladder fibrosis through inducing EMT.…”
Section: The Roles Of Hif-1α In Keloids Formationmentioning
confidence: 99%